2013
DOI: 10.1016/j.foodchem.2013.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Sonicated pineapple juice as substrate for L. casei cultivation for probiotic beverage development: Process optimisation and product stability

Abstract: The aim of this study was to evaluate the use of sonicated pineapple juice as substrate for producing a probiotic beverage by Lactobacillus casei NRRL B442. Maximal microbial viability was found by cultivating L. casei at 31°C and pH 5.8 (optimised conditions). After fermentation, samples of sweetened and non-sweetened juice were stored. After 42 days of storage under refrigeration (4°C), the microbial viability was 6.03 Log CFU/mL in the non-sweetened sample and 4.77 Log CFU/mL in the sweetened sample. The pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 21 publications
7
80
0
5
Order By: Relevance
“…The pH decreased due to lactic acid production and sucrose hydrolysis occurred due to low pH values. These results were in agreement with the previous reports of Costa et al [29]. Otherwise, in liquids, application of high power sonication creates the free radicals such as H + and OH − radicals formed by the decomposition of water inside the cavities [21] [30].…”
Section: Discussionsupporting
confidence: 93%
“…The pH decreased due to lactic acid production and sucrose hydrolysis occurred due to low pH values. These results were in agreement with the previous reports of Costa et al [29]. Otherwise, in liquids, application of high power sonication creates the free radicals such as H + and OH − radicals formed by the decomposition of water inside the cavities [21] [30].…”
Section: Discussionsupporting
confidence: 93%
“…Similar tendency were found in dairy probiotics with 50% and 40% whey, being 0.5% and 0.6% AC, respectively (Thamer & Penna, 2006) and in fermented soymilk-based beverages, with 0.5% to 0.6% AC (Costa et al 2013). Similarly, higher total solid (TS) content for control treatment is due mainly to lipids and carbohydrates contents from integral cow milk.…”
Section: Chemical and Physicochemical Evaluationsupporting
confidence: 67%
“…Consumers are changing their consumption habits for healthier food with lower lipid content (LC), a known characteristic of soybean-based products (Tsuchiya et al, 2006). Similar results were found in soymilk-based fermented beverages (1.8% to 2.0%) by Costa et al (2013). Magalhães et al (2011) studied the chemical composition of Brazilian kefir beverage and showed that during 24 h of fermentation, the protein content increased, while lipid and lactose content decreased.…”
Section: Chemical and Physicochemical Evaluationmentioning
confidence: 67%
See 1 more Smart Citation
“…As mentioned above, we found that L. delbrueckii and L. plantarum could survive the high acidity and low pH in fermented peach juice. Fruit and vegetable juices are not a suitable media for the growth of L. casei and production of probiotic beverages (23). Lactobacillus delbrueckii and L. plantarum are stronger strains than L. casei to survive in pomegranate juice after four weeks in cold storage and high acidity conditions (24).…”
Section: Effect Of Cold Storage On Cell Viabilitymentioning
confidence: 99%